Resilience in Adult Health Science Revisited—A Narrative Review Synthesis of Process-Oriented Approaches - Hiebel, Nina; Rabe, Milena; Maus, Katja; Peusquens, Frank; Radbruch, Lukas; Geiser, Franziska (Frontiers in Psychology, 2021)
Purpose: This article aims to identify how the term “resilience” is addressed in adult health science due to ongoing criticism about the lack of consistency in its conceptualization. Method: Two databases (PubMed and PsycArticles) were searched to retrieve reviews published from 2015 up until 2020 on the general conceptualization of resilience. All reviews had to meet specific inclusion criteria, which resulted in the inclusion of 18 articles. After discussing different conceptualizations regarding the process-oriented approach of resilience in adult health research, we will highlight some mechanisms that are supposed to be involved in the resilience process. Results: Research on resilience in health sciences confronts three core difficulties: defining positive outcome for a processual construct, describing different trajectories within the process, and identifying mechanisms that mediate resilience. Conclusion: The definition of resilience in mental health research as a multidimensional adaptation process is widely accepted, and multiple research paradigms have contributed to a better understanding of the concept. However, the definition of a processual construct in a way that allows for high expert consensus and a valid operationalization for empirical studies remains a challenge. Future research should focus on the assessment of multiple cross-domain outcomes and international and interdisciplinary prospective mixed-method longitudinal designs to fill in the missing links.